Determining factor of muslim tourist’s towards Islamic tourism in Kota Bharu Kelantan / Ahmad Nadzrey Yusuff - Yusuff, Ahmad Nadzrey (2014)
Tourism can be considered as one of major contributions in Malaysia economic and Islamic tourism can be as new tourism destination in Malaysia. The researcher study Muslim tourists’ Motivation towards Islamic tourism in Kota Bharu, Kelantan. There are five (5) factors in the study which are cultural motivation, Islamic learning motivation, recreational motivation, relaxation motivation and socialization motivation. The objective of this study is to identify the important factors that determines the tourist’s motivation towards Islamic Tourism, to determine the most and least important factors that influence tourist’s motivation towards Islamic Tourism, and to determine the relationship between each factors with tourist’s motivation towards Islamic Tourism in Kota Bharu, Kelantan. Then, this study can provide suggestions and recommendations to travel agency and tourism industry on how to attract tourists based on the findings of their motivation in Islamic tourism. Data were gathered from the questionnaires which were distributed to 100 respondents who are guest of hotels, group of tourist follow the trip by bus and the tourist have visit place around Kota Bharu. The data were analyzed using SPSS through the frequencies analysis, cross tabulations analysis, reliability analysis, mean analysis, correlation coefficient analysis and regression analysis. From the analysis, the researcher found that cultural motivation, Islamic learning motivation, recreational motivation, relaxation motivation and socialization motivation have a significant relationship with the Muslim tourist’s motivation. From the findings, it shows that socialization motivation is the most important factors while recreational motivation is the least important factors. Some conclusions are provided in the research and the researcher also stated several recommendations